Structure and Interactions of the TPR Domain of Sgt2 with Yeast Chaperones and Ybr137wp - Krysztofinska, Ewelina M.; Evans, Nicola J.; Thapaliya, Arjun; Murray, James W.; Morgan, Rhodri M. L.; Martinez-Lumbreras, Santiago; Isaacson, Rivka L. (Frontiers in Molecular Biosciences, 2017)
Small glutamine-rich tetratricopeptide repeat-containing protein 2 (Sgt2) is a multi-module co-chaperone involved in several protein quality control pathways. The TPR domain of Sgt2 and several other proteins, including SGTA, Hop and CHIP, is a highly conserved motif known to form transient complexes with molecular chaperones such as Hsp70 and Hsp90. In this work, we present the first high resolution crystal structures of Sgt2_TPR alone and in complex with a C-terminal peptide PTVEEVD from heat shock protein, Ssa1. Using nuclear magnetic resonance spectroscopy and isothermal titration calorimetry, we demonstrate that Sgt2_TPR interacts with peptides corresponding to the C-termini of Ssa1, Hsc82 and Ybr137wp with similar binding modes and affinities.